Evolution of structural and functional diversification among plant Argonautes - Singh, Ravi K (Plant Signal Behav, 2015)
Argonautes (AGOs) are the effector proteins of the RNA-induced silencing (RISC) complex, formed during the phenomena of small-RNA mediated post-transcriptional gene silencing. AGOs are a large family of proteins; their number varies from a few (4 in Chlamydomonas reinhardtii) to many (18 in Oryza sativa) in plants. Genetics-guided analysis have demonstrated the roles of some of the AGOs during growth and development of plants. Biochemical studies have further revealed differences in functional specificities among AGOs. How the AGO family expanded in different plant species during the course of evolution is starting to emerge. We hypothesized that 4 classes of AGOs evolved after divergence of unicellular green algae when an ancestral AGO underwent duplication events. Evolution of multicellularity may have coincided with the diversification of AGOs. A comparative sequence and structure analysis of the plant AGOs, including those from the mosses and the unicellular algae, show not only conformational differences between those from lower and higher plants, but also functional divergence of important sites.